Whole-Genome Sequence of a Reassortant H5N6 Avian Influenza Virus Isolated from a Live Poultry Market in China, 2013 - Qi, Xian (American Society for Microbiology, 2014)
An avian influenza virus, A/environment/Zhenjiang/C13/2013(H5N6), was isolated from a live poultry market in eastern China. Phylogenetic analysis showed that the isolate was a novel reassortant virus with a neuraminidase (NA) gene from H6N6 viruses and the other seven genes from H5N1 viruses, which may pose a potential threat to human and animal health.